A República estável nos Discorsi de Maquiavel - Pierre, Mukabi Misik Senga (2023)
This thesis is entitled “Stable Republic in Machiavelli's Discursos”. The objective of this research is to find, from the reading of Machiavelli's Discourses, the clues that guide towards a stability of the republic. Starting from the geographic conditions of foundation, and going through the virtù of the founders, there are other elements that corroborate for stability. The religion of the Romans (Book I chap. XIII-XV) was an important ally for the maintenance and enforcement of laws. Religion became a very strong instrument for the stability of institutions and ultimately the stability of the republic. It is important to highlight the extent to which the dynamics of political conflicts, causes of eventual changes, are responsible for the creation and conservation of political orders, the guarantee of individual and public freedoms, in short, of political freedoms in general. Corruption at all levels proved to be a barrier to the stability of the republic. Finally, “Machiavelli's Speech on Florence after the death of Lorenzo de Médici Junior”, a text from 1519-1521 that questions why Florence never had a stable republic? This is a beautiful proposal for a republican regime in Florence that closes this thesis. Florence constantly changed governments because there was never a republic or a principality with the necessary qualities. Finally, the mixed republic proved to be an option for political stability.in the city